Elicitation of Needs Using User Personas to Improve Software User Experience - Ahmad Raihan Djamarullah; Wahyu Andhyka Kusuma (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
In the development of a software, the elicitation of requirements in the software development process is a very important phase because at this stage it will determine how a system is made to work properly and according to the plan. User Persona is an HCI technique that works by gathering information about a user to understand the characteristics of that user. The purpose of this research is to solve the problem of uploading practicum modules which are sometimes late so that students or practitioners lack time to study and complete the given practicum assignments. The use of user personas applied at the elicitation stage of software requirements facilitates the needs analysis stage so that it is easier to understand what needs to be developed from the software according to the needs of the user.